2014
DOI: 10.1371/journal.pone.0098346
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Brain Alterations in End Stage Renal Disease Patients on Routine Hemodialysis: A Voxel-Based Morphometry and Resting State Functional Connectivity Study

Abstract: Background and PurposeCognitive impairment is a well-described phenomenon in end-stage renal disease (ESRD) patients. However, its pathogenesis remains poorly understood. The primary focus of this study was to examine structural and functional brain deficits in ESRD patients.Materials and MethodsThirty ESRD patients on hemodialysis (without clinical neurological disease) and 30 age- and gender-matched control individuals (without renal or neurological problems) were recruited in a prospective, single-center st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
3
54
1
Order By: Relevance
“…In the regression analyses with UACR, however, the impact on temporal lobe atrophy was still significant, suggesting that UACR may be a stronger biomarker for neurodegenerative mechanisms, or that the temporal lobe changes may are the first neurodegenerative changes seen in the natural history of the progression of CKD and structural MRI changes. Recent literature on the effect of kidney function on GM suggests that the impact on GM is minimal in mild-moderate stages of CKD and significant in end stage renal disease [8, 35, 36], lending support to our results.…”
Section: Discussionsupporting
confidence: 88%
“…In the regression analyses with UACR, however, the impact on temporal lobe atrophy was still significant, suggesting that UACR may be a stronger biomarker for neurodegenerative mechanisms, or that the temporal lobe changes may are the first neurodegenerative changes seen in the natural history of the progression of CKD and structural MRI changes. Recent literature on the effect of kidney function on GM suggests that the impact on GM is minimal in mild-moderate stages of CKD and significant in end stage renal disease [8, 35, 36], lending support to our results.…”
Section: Discussionsupporting
confidence: 88%
“…Rectal gyrus is the one part of the prefrontal cortex (PFC) and the reduction of GMV in the PFC of hemodialysis patients detected in our study was consistent with the findings reported in previous studies. The hemodialysis patients exhibited GMV reduction in several regions including the bilateral medial orbitofrontal cortex, the bilateral dorsolateral PFC, and the left middle temporal gyrus, as reported by Qiu et al (2014). Ma et al (2014) further showed that the GMV of the bilateral PFC, temporal gyrus, anterior cingulate gyrus, and other widespread regions were decreased in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 67%
“…These results positively correlated with neuropsychologic scores (13)(14)(15)(16). In recent studies (17)(18)(19)(20) of resting-state functional MR imaging, investigators have shown abnormal brain functional connectivity, particularly in the default mode network (DMN), in patients with ESRD. The DMN is believed to be involved in the core processes of human …”
Section: Discussionmentioning
confidence: 95%